2018
DOI: 10.1007/s00253-017-8694-6
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of flavone C-glucosides in engineered Escherichia coli

Abstract: Two plant-originated C-glucosyltransferases (CGTs) UGT708D1 from Glycine max and GtUF6CGT1 from Gentiana triflora were accessed for glucosylation of selected flavones chrysin and luteolin. Uridine diphosphate (UDP)-glucose pool was enhanced in Escherichia coli cell cytosol by introducing heterologous UDP-glucose biosynthetic genes, i.e., glucokinase (glk), phosphoglucomutase (pgm2), and glucose 1-phosphate uridylyltransferase (galU), along with glucose facilitator diffusion protein from (glf) from different or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 64 publications
1
28
0
2
Order By: Relevance
“…The sugar units for disaccharides are rutinose, sophorose, and sambubiose. Some studies have shown the biotransformation of flavonoid glycosides in recombinant E. coli or other microbial cells (Koirala et al., 2014; Pandey et al., 2016; Ruprecht et al., 2019; Shrestha et al., 2018; Wang et al., 2016a). In addition, several nucleotide sugar biosynthetic pathways are engineered in E. coli for regioselective biotransformation and high titer production of flavonoid glycosides (Leonard et al., 2008; Yan et al., 2008).…”
Section: Plant Enzymes Involved In the Biosynthetic Pathway Of Flavonmentioning
confidence: 99%
“…The sugar units for disaccharides are rutinose, sophorose, and sambubiose. Some studies have shown the biotransformation of flavonoid glycosides in recombinant E. coli or other microbial cells (Koirala et al., 2014; Pandey et al., 2016; Ruprecht et al., 2019; Shrestha et al., 2018; Wang et al., 2016a). In addition, several nucleotide sugar biosynthetic pathways are engineered in E. coli for regioselective biotransformation and high titer production of flavonoid glycosides (Leonard et al., 2008; Yan et al., 2008).…”
Section: Plant Enzymes Involved In the Biosynthetic Pathway Of Flavonmentioning
confidence: 99%
“…Although several glucose transporter genes are known in E. coli system, we choose glf - glk system for this study as it is well-characterized and readily available in our lab. Additionally, the working efficiency of this system has been already demonstrated to produce plant polyphenol glycosides and other polyketides in the previous studies [31, 40, 41]. This system increased UDP- d -glucose production, thereby increasing the donor pool for subsequent glycosylation by the At 3GT gene to produce C3G.…”
Section: Discussionmentioning
confidence: 86%
“…Using this approach, several flavonoid glycosides are produced from E. coli. For example, 3-O-rhamosyl quercetin, 3-O-rhamnosyl kaempferol, and 3-O-allosyl quercetin [27], astragalin [28], quercetin-3-O-4-deoxy-4-formamido-L-arabinose [29], quercetin 3-O-N-acetylglucosamine [30], quercetin-3-O xyloside [31] and quercetin 3-O-arabinoside [32], flavonol 3-O-rhamnosides [33,34], flavone 6-C-glucosides [35] are some representative flavonoid glycosides produced from E. coli. Using a similar approach, several polyketide glycosides have been produced from engineered microbial hosts [36].…”
Section: Discussionmentioning
confidence: 99%